Environmental and Chronological Studies of Aegean Coastal Sand Dune Formations. - Zacharias, N.; Evelpidou, N.; Polydorou, M.; Poulos, S.; Tsertos, H.; Michael, C.T.; Bassiakos, I.; Vassilopoulos, A. (37th International Symposium on Archaeometry, 2008)
Optically Stimulated Luminescence (OSL) dating techniques are extensivelly used in nowadays to provide chronological information of sediment material (Zacharias et al., in press) related to landscape evolution caused by natural phenomena or influenced by human activities. Within the present study, OSL was employed to provide the age profile of sand dune formations from Mainland Greece (Peloponnese) and the islands of Crete and Corfu. The application of OSL dating was practised on quartz samples extracted from the sediment material using a modified SAR protocol (Murray and Wintle 2000). The estimation of samples dosimetry was based on gamma- (Tzortzis and Tsertos, 2004) and alpha-spectrometry (Michael and Zacharias, 2000) to provide the U, Th and K concentrations. The so far dating results indicate for ages that fall within Late Holocene to modern periods (4,000 - 500 years). The study will report on the geomorphological, micromorphological and dating results in an attempt to form the environmental and chronological framework of the dune formations in Greece.